Roszczeniowość vs ugodowość. Postawy rodzicielskie w środowiskach szkolnych z perspektywy teorii reprodukcji społeczno-kulturowej Pierre’a Bourdieu - Marta, Jurczak-Morris (Studia Edukacyjne, 2017)
School is a unique environment of social interactions. It generates the variety of attitudes and behaviours. This paper demonstrates differences in the attitudes towards school of parents, according to their social status. The research study emphasises that social class is one of the key determinants of ways in which parents participate in their children’s education process. Likewise, it shows that educational aspirations of a certain group of parents, as well as their vision of what education should look like vary and make up specific‘class patterns’ of parental participation in education. This qualitative rese-arch clarifiesthat most parents from advantaged social background have a clear vision on education as well as expectations towards school. They are therefore more likely to demand and complain. On the contrary, parents from a lower social class tend to be conciliatory, unquestionably trusting the school institution.